Orientations of Avicenna's philosophy - Gutas, Dimitri. ([S.l.])
1 online resource.
Keywords: The volume brings together seventeen studies on Avicenna by Dimitri Gutas, written over the past twenty-five years. They aim to establish Avicenna's historical and philosophical context as a means to determining his philosophical project and the orientations of his thought. They deal with his life and works, his method, his epistemology, and his later reception in the Islamic world, ending with a programmatic essay on the state of the field of Avicennan studies and future agenda. Occasioned by issues raised in Gutas's monograph on Avicenna and the Aristotelian Tradition (whose second edition has just appeared), they form a substantive complement to it. For this reprint, a number of the essays have been reset and accordingly revised and updated. Provided with exhaustive indexes of names, places, subjects, and technical terms, the volume constitutes a new and major research tool for the study of Avicenna and his heritage.